Opioid analgesic administration in patients with suspected drug use - Maria Clara Giorio Dutra Kreling; Cibele Andrucioli de Mattos-Pimenta
ABSTRACT Objective: To identify the prevalence of patients suspected of drug use according to the nursing professionals' judgement, and compare the behavior of these professionals in opioid administration when there is or there is no suspicion that patient is a drug user. Method: A cross-sectional study with 507 patients and 199 nursing professionals responsible for administering drugs to these patients. The Chi-Square test, Fisher's Exact and a significance level of 5% were used for the analyzes. Results: The prevalence of suspected patients was 6.7%. The prevalence ratio of administration of opioid analgesics 'if necessary' is twice higher among patients suspected of drug use compared to patients not suspected of drug use (p = 0.037). Conclusion: The prevalence of patients suspected of drug use was similar to that of studies performed in emergency departments. Patients suspected of drug use receive more opioids than patients not suspected of drug use.